ANALISIS KESUKSESAN SISTEM TEKNOLOGI INFORMASI: Studi System Application Product (SAP) PT Freeport Indonesia. - , Austin Danduru, Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the relationship of information quality, system quality with the use of the system